Cell‐Like Nanostructured Environments Alter Diffusion and Reaction Kinetics in Cell‐Free Gene Expression. Issue 3 (17th December 2015) - Hansen, Maike M. K.; Paffenholz, Sabine; Foschepoth, David; Heus, Hans A.; Thiele, Julian; Huck, Wilhelm T. S.
Abstract: In highly crowded and viscous intracellular environments, the kinetics of complex enzymatic reactions are determined by both reaction and diffusion rates. However in vitro studies on transcription and translation often fail to take into account the density of the prokaryotic cytoplasm. Here we mimic the cellular environment by using a porous hydrogel matrix, to study the effects of macromolecular crowding on gene expression. We found that within microgels gene expression is localized, transcription is enhanced up to fivefold, and translation is enhanced up to fourfold. Our results highlight the need to consider the role of the physical environment on complex biochemical reactions, in this case macromolecular crowding, nanoscale spatial organization, and confinement. Abstract : Having room to express yourself : Based on Michaelis–Menten kinetics, we show that gene expression in unconfined bulk solution is inhibited by macromolecular crowding, whereas it is enhanced in DNA‐functionalized microgels. The results emphasize the importance of geometry‐controlled kinetics when mimicking biological functions.